Influence Loyalty Work & Satisfaction Work On Performance Employee Which In Mediation By Motivation Work In Pks PT PP Starch Sari District Aceh Tamiang - Risha Ramadani; Emi Wakhyuni (Yayasan Multidimensi Kreatif, 2025)
Employees and their performance are the main assets that determine the success and sustainability of an organization amidst increasingly competitive global competition. This study aims to analyze the effect of work loyalty and job satisfaction on employee performance mediated by work motivation on employees at the Palm Oil Mill (PKS) of PT PP Pati Sari, Aceh Tamiang Regency. This study was conducted considering the important role of work loyalty, job satisfaction, and work motivation in improving employee performance as part of organizational success. This study uses a quantitative approach with an explanatory research type. Data were collected through questionnaires distributed to employees of PKS PT PP Pati Sari. The population in this study were all employees working at the company, with a sampling technique using the purposive sampling method. The research sample consisted of 104 respondents. Data analysis was carried out using SmartPLS (Partial Least Square) software to test the relationship between variables, both directly and indirectly, and to test the mediating effect of work motivation. The results showed that work loyalty had a significant positive effect on employee performance, with a coefficient value of 0.152 and a P-value of 0.019. Job satisfaction also has a significant positive effect on employee performance (coefficient 0.253, P-value 0.000). In addition, work loyalty has a significant effect on work motivation (coefficient 0.414, P-value 0.000), and job satisfaction has a significant effect on work motivation (coefficient 0.446, P-value 0.000). Work motivation is proven to have a significant effect on employee performance (coefficient 0.567, P-value 0.000). Furthermore, work motivation mediates the effect between work loyalty and job satisfaction on employee performance with a significant coefficient value (0.235 to 0.253) and P-value <0.05.